Evaluation of the processability of boron‐containing organosilazane polymers based on shear rheology. Issue 1 (27th June 2012) - Ouyang, Ting; Gottardo, Laura; Bernard, Samuel; Chiriac, Rodica; Balan, Corneliu; Miele, Philippe
Abstract The shear rheology of boron‐containing organosilazane polymers has been investigated in detail with a double objective. The first objective was to evaluate their processability to form fibers by melt‐spinning, and the second objective was to predict their molecular structure. We focused on a representative type of boron‐containing organosilazane polymers called boron‐modified polysilazanes (BmPSs) with the ideal structure [B(C2H4SiCH3NCH3)3]n (C2H4 = CHCH3, CH2CH2). Characterization tools showed that their viscous and elastic properties are strongly affected by molecular parameters fixed during synthesis and in particular by the methylamine (MA) : tris(dichlorosilylethyl)borane (TDSB) molar ratio imposed during their synthesis. In the spinning domain, the frequency dependences of the storage and loss moduli showed that the prerequisite conditions for obtaining polymer fibers are fulfilled with samples having 9.0 ≤ MA : TDSB molar ratios ≤ 9.7. However, the presence of thickening in the computed extensional viscosity function and the loss of cohesion of filament derived from samples with MA : TDSB ratio > 9.2 during drawing put in evidence the best potential of polymers with 9 ≤ MA : TDSB ratio ≤ 9.2 to generate fine‐diameter solid filaments in a stable process. Based on rheological tests, the molecular structure of BmPSs has been tentatively predicted in relation with the MA : TDSB ratio. The increase of the latter favored the disentanglement of the polymer framework, and we postulated that it lowered the molecular weight. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013